Bridging gaps in rapid response systems. Issue 12 (December 2016) - Douglas, Mark; DeVita, Michael A.; Gilder, Richard; Lauer, Pamela
Abstract : This study identifies existing disparities in rapid response team implementation and education across Texas hospitals.